(untitled) (Journal of Pharmaceutical Negative Results, 2023)
A 7-year-old girl presenting with recurrent febrile urinary tract infection (UTI) underwent a right low upper to lower ureteroureterostomy (UU) for right duplex system ureterocele (DSU) with promising short-term results.